Sperm mitochondria dysfunction in response to testicular cancer - Qasemi, Maryam; Sur, Vishma Pratap; Simonik, Ondrej; Postlerova, Pavla; Skrobanek, Pavel; Hradec, Tomas; Boublikova, Ludmila; Zamecnik, Libor; Buchler, Tomas; Neuzil, Jiri; Komrsková, Kateřina (European journal of clinical investigation, 2024)
Testicular cancer is the most common form of cancer in young men of reproductive age and its incidence is increasing globally. With the currently successful treatment and 95% survival rate, there is a need for deeper understanding of testicular cancer-related infertility. Most patients with testicular cancer experience semen abnormalities prior to cancer therapy. However, the exact mechanism of the effect of testicular cancer on sperm anomalies is not known. Mitochondria are organelles that play a crucial role in both tumorigenesis and spermatogenesis and their malfunction may be an important factor resulting in sperm abnormalities in testicular cancer patients. Within the scope of this review, we will discuss current knowledge of testicular cancer-related alterations in the ATP production pathway, a possible pathophysiological switch from oxidative phosphorylation (OXPHOS) to glycolysis, as well as the role of oxidative stress promoting sperm dysfunction. In this regard, the review provides a summary of the impact of testicular cancer on sperm quality as a possible consequence of impaired mitochondrial function including the energy metabolic pathways that are known to be altered in the sperm of testicular cancer patients.
Keywords: Spermatozoa; sperma; testikulární nádory; Mitochondrial Diseases; Semen Analysis; lidé; Testicular Neoplasms; germinální a embryonální nádory; Humans; Semen; spermie; analýza spermatu; Male; mužské pohlaví; Neoplasms, Germ Cell and Embryonal; mitochondriální nemoci